Batman: Arkham Asylum - a cultural icon seen through the looking glass - Smith, David (My University, 2016)
This dissertation examines how particular combinations of image and text in sequential art reflect specific social, historical and political contexts. The analysis of how meaning is constructed is done through consideration of three iterations of the Batman superhero character, and argues for an eventual postmodernisation of the character. The first case study presented is the original version of Batman as it debuted in 1939, which naturally established much of the substance from which later depictions would take their cues. The second case study used is the “camp” 1960s TV series starring Adam West, which was influenced by the highly restricted Batman comics under the Comics Code Authority established in 1954. The main case study, and the central focus of this dissertation, is Batman – Arkham Asylum (1989), a graphic novel by Grant Morrison and Dave McKean, the latest of the three iterations, which represents the eventual disruption of the enforced or constructed harmony evident in the earlier versions of the character into a fracturing and fragmentation both of the world and the self. It is a version of Batman that privileges the interiority and psychological complexity of the character, representing a culmination of the 1980s shift toward a more mature audience with its incorporation of horror, violence and mental turmoil. These three examples are compared and contrasted, showing how each constructs a particular meaning using its own unique combination of image and text. Having established a historicity for the character and having constructed an argument for how Batman as a cultural icon echoes shifts in society, the focus of the dissertation is transferred to a deeper analysis of Arkham and attempts to trace more explicitly its status as a postmodern text by examining its fragmentary nature, its use of intertextuality and how meaning in Arkham is constructed in the mind. Following this, an exploration of the central theme of madness in the graphic novel is provided in order to show how the work both critiques the representation of madness in fiction as well as how the liminal setting of the asylum functions as part of the postmodernisation of Batman by creating a “landscape of madness” where irrationality and the uncanny dominate reality, in contrast to the logical, “left-brain” treatment of Batman which had become common prior to Arkham Asylum. The analysis of the three iterations is shaped by WTJ Mitchell’s theories on imagetext relationships and additionally by the principles of sequential art outlined by Scott McCloud. The postmodern theoretical framework is informed by John Docker’s explorations of fragmentation, intertextuality, inversion and the Carnivalesque. Additionally, the writings of Lillian Feder and Michel Foucault will inform the discussion of madness in Arkham.
Thesis (M.A. (English))--University of the Witwatersrand, Faculty of Humanities, 2016.
Keywords: Batman (Fictitious character); Joker (Fictitious character)--Comic books, strips, etc.; Graphic novels--History and criticism; Comic books, strips, etc.--History and criticism; Psychiatric hospitals--Comic books, strips, etc.